The transition to harm reduction: understanding the role of non-governmental organisations in Malaysia - Narayanan, S.; Vicknasingam, B.; Robson, Noorzurani (Elsevier, 2011)
Background The transition of drug policy from prohibition to harm reduction has never been easy. The deeply entrenched belief in prohibition shared by policy makers and religious leaders provided little room for alternatives, and change came only slowly. The non-governmental organisations (NGOs) in Malaysia played a pivotal role in effecting such a change. Understanding how they did so may be instructive for other similarly placed countries.